Sosialisasi Dan Praktik Perilaku Hidup Bersih Dan Sehat Dalam Upaya Pencegahan Stunting Di Desa Panawangan Kabupaten Ciamis - Nuraeani, Yeni; Dewi, Rani; Farhan Syafiq, Hary (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Panawangan Village faces four main issues that are the focus of the Thematic Community Service Program (KKN) implementation: high stunting rates. The first issue is the lack of education regarding stunting prevention in toddlers. This activity aims to raise parental awareness of the importance of nutritional intake in supporting optimal child growth and development. The Thematic Community Service Program aims to identify existing problems and offer innovative and sustainable solutions to improve the welfare of the village community. The following outcomes were achieved: Outreach activities successfully reached all hamlets in Panawangan Village with active community participation. Oral evaluations demonstrated an increase in participants' understanding of the concept of stunting and the importance of nutrition for children; The formation of a waste bank management group in Cigobang Hamlet; Increased community awareness of the importance of waste sorting and household waste reduction; and A record number of waste collected and processed during the activity.